Higher Education and the Issue of Disability : from the Breaking Down of Barriers to Intercollegiate Forms of Cooperation - Filek, Janina (Studia Oeconomica Posnaniensia, 2015)
The article, on the one hand, is an attempt to point out the difficulties faced by universities in the field of implementation of the forms of educational support addressed to students with disabilities, and, on the other , it is a presentation of some good practices which have been implemented in the academic environment of Krakow within the cooperation amongst six universities in the same field.